Młodopolski spór o Sienkiewicza. Kampania oskarżycielska „Głosu” i reakcje obrońców Litwosa - Fiołek, Krzysztof (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2020)
The work presents the polemical campaign of progressive Warsaw journalists against Sienkiewicz, one that played out in 1903 on the columns of the weekly Głos. The polemic presented their functions not only in respect to Literary Studies. It was also an integral part of the polemic over the assessment of the nobility’s heritage as well as a source of questions on a new formula of Polish identity – one viewed in terms of psychology, esthetics, life style and social organisation. The anthology contains both the texts of those attacking and defending Sienkiewicz, calls to uphold fundamental principles and to honour God and country, as well as that of pamphlets and libelous pasquinades.
The Młodopolska Polemic Over Sienkiewicz. The Głos Campaign of Accusations and Reaction of Those Championing Litwos
Praca powstała w ramach projektu badawczego NPRH nr 11H 16 0131 84.